Methodological challenges of measuring brain volumes and cortical thickness in idiopathic normal pressure hydrocephalus with a surface-based approach - Del Giovane, Martina; David, Michael C. B.; Kolanko, Magdalena A.; Gontsarova, Anastasia; Parker, Thomas; Hampshire, Adam; Sharp, David J.; Malhotra, Paresh A.; Carswell, Christopher (Frontiers in Neuroscience, 2024)
Identifying disease-specific imaging features of idiopathic Normal Pressure Hydrocephalus (iNPH) is crucial to develop accurate diagnoses, although the abnormal brain anatomy of patients with iNPH creates challenges in neuroimaging analysis. We quantified cortical thickness and volume using Freesurfer 7.3.2 in 19 patients with iNPH, 28 patients with Alzheimer's disease (AD), and 29 healthy controls (HC). We noted the frequent need for manual correction of the automated segmentation in iNPH and examined the effect of correction on the results. We identified statistically significant higher proportion of volume changes associated with manual edits in individuals with iNPH compared to both HC and patients with AD. Changes in cortical thickness and volume related to manual correction were also partly correlated with the severity of radiological features of iNPH. We highlight the challenges posed by the abnormal anatomy in iNPH when conducting neuroimaging analysis and emphasise the importance of quality checking and correction in this clinical population.